Badminton injuries in youth competitive players - Goh, S.L.; Mokhtar, A.H.; Mohamad Ali, M.R. (Edizione Minerva Medica, 2013)
Aim: The aim of the study was to examine sports injury pattern and establish cost of injuries in relation to training of 58 competitive badminton players in a Malaysian National Sports School. Methods: This one-year prospective observational study recruited all the 13-16 year old students after obtaining informed consent from their appointed guardian. All participants were requested to report any injuries, which were pain or disabilities that occur within the study period (September 1, 2008 to August 31, 2009) either during training or competition. Injured students were to seek treatment from the researcher(s) who made weekly visits and they were then followed up accordingly until they return to full training. Details and progress of the injuries were documented during each visit. Results: Sixty-three injuries were recorded. Soft tissue sprains/strains were the commonest injury (64%). About one third of the injuries occurred in the lower limb especially the knees and was followed by back injuries; 38% of the injuries did not require training modification, half of these injuries resumed training within one week. Upon full training, half of them were still symptomatic. Injury risk was 57%; injury rate was 0.9 injuries/ player/1000 training hours. Conclusion: Badminton injuries mostly involved the lower limb and almost all overuse injuries occurred in the lower limb. However, badminton injuries as a whole were predominantly sprains and strains, and not overuse in nature as widely believed.